2021
DOI: 10.1111/cei.13663
|View full text |Cite
|
Sign up to set email alerts
|

Altered peripheral B lymphocyte homeostasis and functions mediated by IL‐27 via activating the mammalian target of rapamycin signaling pathway in patients with rheumatoid arthritis

Abstract: B cell dysfunction and inflammatory cytokine over‐production participate in the pathogenesis of rheumatoid arthritis (RA). Here we compared peripheral B cell homeostasis and immune functions between RA patients and healthy controls (HC) and explored vital signaling pathways involved in altered RA B cells. We found that RA patients showed significantly decreased frequencies of peripheral CD19+CD27+CD24high regulatory B (Breg) cells but increased frequencies of CD19+CD27+CD38high plasmablasts and CD19+CD138+ pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…These observations suggest a possible enhancement of mTOR‐I on the immune response to mRNA vaccines. To date, limited reports suggest that inhibition of mTOR could restore B cell homeostasis and functions in autoimmune diseases 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest a possible enhancement of mTOR‐I on the immune response to mRNA vaccines. To date, limited reports suggest that inhibition of mTOR could restore B cell homeostasis and functions in autoimmune diseases 17 …”
Section: Discussionmentioning
confidence: 99%
“…To date, limited reports suggest that inhibition of mTOR could restore B cell homeostasis and functions in autoimmune diseases. 17 …”
Section: Discussionmentioning
confidence: 99%
“…As far as B lymphocyte subsets are concerned, a broad characterisation of seropositive RA B cell phenotype and their activities demonstrated that these cells secrete less IL-10 after in vitro activation, and they decreased their plasma cell differentiation frequency and IgM production. Furthermore, it has also been observed an increased number of atypical CD27-IgM-IgD-CD21-B lymphocytes (78), a reduced level of CD19 + CD27 + CD24 high Breg cells with higher proportions of circulating CD19 + CD27 + CD38 high plasmablasts (79). Finally, with regard to autoantibodies and based on the knowledge that antimodified protein antibodies (AMPA) IgG display cross-reactivity to multiple post-translational modifications, AMPA-IgM from RA patients were shown to exert the same cross-reactivity features of AMPA IgG and were also more potent then AMPA-IgG in complement-activation (80).…”
Section: Adaptive Immune Responsementioning
confidence: 99%
“…• RA-T-cells, B-cells and plasmacells are able to drive RANKL-dependent osteoclast differentiation (68,69). • In RA CD27-IgM-IgD-CD21-B lymphocytes are increased while CD19 + CD27 + CD24 high Breg cells with higher proportions of circulating CD19 + CD27 + CD38 high plasmablasts are reduced (79).…”
Section: Take Home Messagesmentioning
confidence: 99%
“…Circulating IL-27 is elevated in RA patients and can in uence RA development by regulating synovial broblasts and various immune cell responses [16][17][18]. Our previous study has demonstrated that increased IL-27 could promote RA B cell dysfunction via activating the mTOR signaling pathway [19], which indicates that IL-27 signaling may induce RA B cell hyperactivation by controlling cellular metabolism. However, further researches still need to be done.…”
Section: Introductionmentioning
confidence: 99%